A carbon-based coating for a tool surface, a method for producing the same, and a tool

CN117604451BActive Publication Date: 2026-10-30SHENZHEN JINZHOU PRECISION TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311679967.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2026-10-30
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

[0007]针对现有技术存在的问题,本发明的目的在于提供一种用于刀具表面的碳基涂层、其制备方法及刀具,所述碳基涂层根据sp3键和sp2键含量的不同,分别设置以sp3键或sp2键为主的碳层,前者提供较高的硬度和耐磨性,后者摩擦系数低,具备较好的润滑性;并在两者之间设置渐变层,使得两者的性质能够实现渐变过渡,避免因性质相差较大而造成结合性较差,容易分层或破损的问题,提高碳基涂层的稳定性

Benefits of technology

[0085](1)本发明根据sp3键和sp2键含量的不同,分别设置以sp3键和sp2键为主的碳层,前者提供较高的硬度和耐磨性,后者摩擦系数低,具备较好润滑性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117604451B_ABST
    Figure CN117604451B_ABST
Patent Text Reader

Abstract

The application provides a carbon-based coating for a tool surface, a preparation method of the carbon-based coating and a tool. 3 sp 2 sp 3 sp 3 sp 2 sp 2 sp 3 sp 3 sp 2 sp The carbon-based coating has the advantages that the carbon-based coating is simple in structure, stable in performance, low in cost and wide in application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cutting tool coating technology, and relates to a carbon-based coating for the surface of cutting tools, its preparation method, and the cutting tool thereof. Background Technology

[0002] Printed circuit boards (PCBs) are the carriers of the modern information industry. As information transmission evolves towards higher frequency, higher speed, and lower loss, the thickness of PCBs and the proportion of hard fillers are gradually increasing, along with the number of micro-holes and the viscosity of modified resins. This leads to accelerated wear of micro-drills used in mechanical drilling, difficulties in chip removal, and in severe cases, tool breakage, affecting the processing efficiency and quality of PCBs. Therefore, it is necessary to improve the wear resistance of micro-tools to increase their service life, while simultaneously ensuring high lubricity of the drill bit surface to enhance chip removal performance and prevent tool breakage caused by dust clogging.

[0003] Coating technology is one of the most effective means to improve the surface properties of materials. The performance requirements for coatings typically include hardness, wear resistance, and coefficient of friction. Existing wear-resistant coatings are usually metal or ceramic coatings, such as TiAlN, CrAlN, or TiSiN. While these coatings have high hardness and excellent wear resistance, they also have high coefficients of friction, making them prone to wear and unable to meet good chip removal requirements. Diamond-like carbon (DLC) coatings, as a novel type of coating, include tetrahedral carbon coatings and possess high hardness and low coefficient of friction, making them widely used in tool coating. However, their high internal stress and the risk of breakage when the coating is thickened limit the ability to produce large-thickness coatings. Conversely, thinner coatings offer limited improvement in the wear resistance of tools, affecting their service life.

[0004] CN 101432462A discloses a substrate coated with a multilayer structure comprising a tetrahedral carbon layer and a softer outer layer. The multilayer structure includes an adhesion-promoting layer, an intermediate layer, and an amorphous carbon layer. The intermediate layer comprises a tetrahedral carbon layer with a Young's modulus higher than 200 GPa and an sp2 content higher than 50%. 3 The bonded carbon fraction, including non-hydrogenated tetrahedral carbon or hydrogenated tetrahedral carbon, has a Young's modulus of less than 200 GPa for the amorphous carbon layer and has a sp content of less than 40%. 3 The bonded carbon fraction includes amorphous hydrogenated carbon or diamond-like carbon nanocomposite layers. In this multilayer structure, the tetrahedral carbon layer and the amorphous carbon layer are in direct contact, and the performance changes of the two are relatively abrupt, which can easily lead to a weakening of the bonding strength. During application, the structural layers are prone to breakage or separation, affecting the service life.

[0005] CN 103317793A discloses a diamond-like carbon (DLC)-based nanocomposite coated cutting tool and its preparation method. The tool substrate has a connecting layer, a gradient layer, and a main wear-resistant layer sequentially attached from the inside out. The connecting layer is molybdenum, and the gradient layer, a Mo-C layer, is attached to the connecting layer, with the carbon content gradually increasing from the inside out. The main wear-resistant layer is attached to the gradient layer and is a diamond-like carbon coating doped with molybdenum carbide, i.e., a MoC-DLC layer. The DLC coating in this composite coating is located on the outermost layer, and this structural layer mainly serves a wear-resistant function, but it still belongs to the sp. 3 Structural layers with high bond content have greater internal stress, and thickening the coating can easily cause breakage, making it impossible to achieve long-term wear resistance and resulting in a short lifespan.

[0006] In summary, the selection of carbon-based coatings for tool surfaces needs to be based on SP... 3 Key and sp 2 By leveraging the properties of the bonds and setting different carbon-based structural layers, while ensuring hardness and wear resistance, a low coefficient of friction is achieved, lubricity is improved, and a large thickness of coating deposition is realized. Summary of the Invention

[0007] To address the problems existing in the prior art, the present invention aims to provide a carbon-based coating for the surface of a cutting tool, its preparation method, and the cutting tool thereof, wherein the carbon-based coating is prepared according to SP... 3 Key and sp 2 Different bond contents are set to sp 3 key or sp 2 The carbon layer is mainly composed of bonds, with the former providing high hardness and wear resistance, and the latter having a low coefficient of friction and good lubricity; a gradient layer is set between the two to allow for a gradual transition in their properties, avoiding problems such as poor bonding, easy delamination or damage caused by large differences in properties, and improving the stability of the carbon-based coating.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a carbon-based coating for a cutting tool surface, the carbon-based coating comprising, from the cutting tool surface outwards, a high content of sp... 3 Bonded carbon layer, gradient layer and high sp content 2 Bonded carbon layer, the high content of sp 3 sp 3 The bond content is 50%–80%, for example, 50%, 55%, 60%, 65%, 70%, 75%, or 80%, etc., and the high content of sp... 2 sp 2The bond content is 50%–80%, for example, 50%, 55%, 60%, 65%, 70%, 75%, or 80%, but not limited to the listed values; other unlisted values ​​within their respective ranges also apply; the gradient layer, from the inside out, sp 3 From high to low bond content, sp 2 The bond content increases from low to high.

[0010] In this invention, the structure of the carbon-based coating on the tool surface is selected based on its performance requirements, and high content of sp is set accordingly. 3 Bond and high content of sp 2 Carbon layers of bonds, sp. carbon 3 The bond has a diamond structure, and carbon has sp bonds. 2 The bonds are graphite structures, and the different ratios of the two will affect the coating performance. The former is located on one side of the tool substrate, sp 3 It has a high bond content, high hardness, and excellent wear resistance; the latter is located on the air side, sp 2 With a higher bond content, a lower coefficient of friction, and superior lubrication performance, this invention incorporates a gradient layer, i.e., sp, between the two components. 3 Key and sp 2 The bond content changes gradually to achieve a transition in performance between the two carbon layers, avoiding the problem of poor bonding caused by large performance differences, improving the stability of the carbon-based coating, and reducing the internal stress in the coating to avoid the risk of easy breakage due to coating thickness, thus achieving large thickness deposition; the carbon-based coating has a simple structure, stable performance, low cost, and wide range of applications.

[0011] In this invention, sp in the carbon layer 3 The bond content test includes: sp content of carbon layers at different depths from the coating surface towards the tool direction. 3 The bond content is determined by etching a carbon-based coating to a specific thickness using argon ions to obtain a carbon-based coating surface of corresponding depth, followed by X-ray photoelectron spectroscopy to measure the sp bond content. 3 Carbon-containing coatings with sp bonds 3 Key and sp 2 The proportion of the total amount of bonds.

[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The technical objectives and beneficial effects of the present invention can be better achieved and realized through the following technical solutions.

[0013] As a preferred technical solution of the present invention, the high content of sp 3The thickness of the bonded carbon layer is 0.1 to 5 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0014] Preferably, the high content of sp 3 The hardness of the bonded carbon layer is 45 to 65 GPa, such as 45 GPa, 50 GPa, 55 GPa, 60 GPa or 65 GPa, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0015] Preferably, the high content of sp 2 The thickness of the bonded carbon layer is 0.1 to 5 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0016] Preferably, the high content of sp 2 The hardness of the bonded carbon layer is 20–45 GPa, such as 20 GPa, 25 GPa, 30 GPa, 35 GPa, 40 GPa or 45 GPa, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0017] In this invention, the hardness of the carbon layer is obtained by detecting a nanoindentation instrument.

[0018] Preferably, the thickness of the gradient layer is 0.1 to 3 μm, such as 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0019] Preferably, the sp in the gradient layer 3 Bond content increased from high sp content 3 sp 3 The content of the bond decreased to a high content of sp 2 sp 3 Bond content.

[0020] Preferably, the sp in the gradient layer 3 Bond content or sp 2 The bond content changes continuously or gradually.

[0021] Preferably, during the continuous gradual change, sp 3 Bond content or sp 2The bond content changes linearly or nonlinearly.

[0022] Preferably, during the gradient transition, the gradient layer consists of at least two sp layers. 3 It consists of gradient layers with different bond contents.

[0023] Preferably, the thickness of a single gradient layer is 0.02 to 1 μm, such as 0.02 μm, 0.05 μm, 0.1 μm, 0.3 μm, 0.5 μm, 0.6 μm, 0.8 μm or 1 μm, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0024] In this invention, as the gradient layer contains sp 3 Bond content or sp 2 Changes in bond content lead to changes in hardness, with the following trend: sp 3 The bond content decreases continuously or in a gradient, while sp 2 As the bond content increases continuously or in a gradient, the hardness of the coating gradually decreases; that is, the hardness of the coating is controlled by adjusting the sp bond content in the gradient layer. 3 Key and sp 2 The proportion of bonds in the coating achieves a gradual transition, which can be divided into continuous gradient and gradient gradient; in continuous gradient, sp 3 The bond content decreases along the thickness direction, and the rate curve can be linear and uniform or nonlinear, as shown in the following example. Figure 1 As shown, during gradient gradation, the gradient layer consists of multiple sp... 3 The structure is composed of structural layers with different bond contents, and there are sps between adjacent gradient layers. 3 The difference in bond content and the thickness of the monolayer can be equal or unequal, as shown in the following examples. Figure 2 As shown.

[0025] In this invention, the hardness of the carbon-based coating is 20–65 GPa, for example 20 GPa, 25 GPa, 30 GPa, 35 GPa, 40 GPa, 45 GPa, 50 GPa, 55 GPa, 60 GPa or 65 GPa, and the overall thickness is 0.5–8 μm, for example 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm.

[0026] As a preferred technical solution of the present invention, the high content of sp 2 The bonded carbon layer includes a pure carbon coating or an element-doped carbon coating.

[0027] Preferably, the doped element includes any one or a combination of at least two of silicon, nitrogen, hydrogen, chromium, titanium, tantalum, molybdenum, niobium, or aluminum. Typical but non-limiting examples of such combinations include: combinations of silicon and nitrogen, combinations of chromium and titanium, combinations of nitrogen and aluminum, combinations of silicon, titanium, and tantalum, combinations of tantalum, molybdenum, and niobium, etc.

[0028] Preferably, the carbon-based coating further includes an adhesive layer located between the carbon-based coating and the tool surface.

[0029] Preferably, the material of the adhesive layer includes any one or a combination of at least two of the following: an element, a nitride of the corresponding element, a carbide of the corresponding element, or a carbonitride of the corresponding element. Typical but non-limiting examples of such combinations include: a combination of an element and a nitride of the corresponding element, a combination of a nitride of the corresponding element and a carbide of the corresponding element, a combination of a carbide of the corresponding element and a carbonitride of the corresponding element, and a combination of an element, a nitride of the corresponding element, and a carbide of the corresponding element, etc.

[0030] Preferably, the element includes any one or a combination of at least two of chromium, titanium, molybdenum, tungsten, tantalum, vanadium, or silicon. Typical but non-limiting examples of such combinations include: combinations of chromium and titanium, combinations of tungsten and tantalum, combinations of titanium and silicon, combinations of molybdenum, tungsten, and tantalum, etc.

[0031] Preferably, the number of adhesive layers is at least one, such as one, two or three layers, and the thickness of each adhesive layer is 0.1 to 1 μm, such as 0.1 μm, 0.3 μm, 0.5 μm, 0.6 μm, 0.8 μm or 1 μm, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0032] In this invention, an adhesive layer is provided to improve the bonding force between the carbon-based coating and the tool surface. The adhesive layer can be one or more layers, and the multiple layers can be a combination of different materials.

[0033] Secondly, the present invention provides a method for preparing the above-mentioned carbon-based coating, the method comprising the following steps:

[0034] (1) After fixing the tool drill bit, a vacuum is drawn and a protective gas is introduced to control the pressure. The magnetron sputtering cathode and the magnetically modulated multi-arc cathode are turned on, and the cathode current is controlled to deposit a high content of sp on the surface of the tool drill bit. 3 Bonded carbon layer;

[0035] (2) Based on step (1), the current of the magnetron sputtering cathode is continuously increased and the current of the magnetically controlled multi-arc cathode is continuously decreased to deposit a gradient layer.

[0036] (3) Based on step (2), continue to control the current of the magnetron sputtering cathode and the magnetically controlled multi-arc cathode to deposit a high-content sp2. 2 A carbon layer is bonded to obtain a carbon-based coating.

[0037] In this invention, sp in the carbon-based coating 3 Key and sp 2Bond content control is achieved by adjusting the ratio of carbon atoms to carbon ions reaching the tool surface. A higher proportion of carbon atoms results in a higher concentration of sp(s) in the coating. 2 The higher the bond content, the greater the proportion of carbon ions, and the higher the sp content in the coating. 3 The higher the bond content, the more carbon atoms are obtained through glow discharge from a magnetron sputtering cathode. The greater the current or power of the magnetron sputtering cathode, the more carbon atoms are produced. Carbon ions are obtained through arc discharge from a magnetically regulated multi-arc cathode. The greater the current or power of the magnetically regulated multi-arc cathode, the more carbon ions are produced. That is, the ratio of carbon atoms to carbon ions requires the coordinated control of the two types of cathodes. A certain angle is formed between the magnetron sputtering cathode and the magnetically regulated multi-arc cathode. The angle range can be selected from 20 to 180 degrees, such as 20 degrees, 40 degrees, 60 degrees, 90 degrees, 120 degrees, 135 degrees, 150 degrees, or 180 degrees. The angle between their central axes intersects near the surface of the tool, ensuring that carbon atoms and carbon ions reach the surface simultaneously, rather than being deposited sequentially. In addition, the magnetron sputtering cathode and the magnetically regulated multi-arc cathode are arranged in pairs. Multiple pairs can be set according to the equipment structure and coating requirements, and they are arranged on the outer periphery of the equipment.

[0038] As a preferred technical solution of the present invention, the tool drill bit in step (1) is cleaned before being fixed, and the cleaning includes ultrasonic cleaning.

[0039] Preferably, the cleaning medium includes any one or a combination of at least two of acetone, alcohol, or water. Typical but non-limiting examples of such combinations include: a combination of acetone and alcohol, a combination of alcohol and water, and a combination of acetone, alcohol, and water. Preferably, the three are used in sequence, and the medium is used alone.

[0040] Preferably, the cleaning time is independently 10 to 60 minutes, such as 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes or 60 minutes, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0041] Preferably, the cutting tool / drill bit is dried after cleaning.

[0042] Preferably, the cutting tool in step (1) is placed in a vacuum chamber and fixed on a fixture.

[0043] Preferably, the pressure drops to 1.0 × 10⁻⁶ after vacuuming in step (1). -2 Below Pa, for example, 1.0 × 10 -2 Pa, 8.0×10 -3 Pa, 6.0×10 -3 Pa, 5.0 × 10 -3 Pa, 4.0 × 10 -3 Pa, 2.0×10 -3Pa or 1.0 × 10 -3 Pa, etc., but not limited to the listed values; other unlisted values ​​within this range also apply.

[0044] Preferably, the protective gas in step (1) includes an inert gas.

[0045] Preferably, the pressure after the protective gas is introduced in step (1) is 0.1 to 5 Pa, such as 0.1 Pa, 0.5 Pa, 1 Pa, 1.5 Pa, 2 Pa, 2.5 Pa, 3 Pa, 4 Pa ​​or 5 Pa, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0046] Preferably, the current of the magnetron sputtering cathode in step (1) is 0.1 to 2A, such as 0.1A, 0.3A, 0.5A, 0.8A, 1A, 1.2A, 1.5A, 1.8A or 2A, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0047] Preferably, the power of the magnetron sputtering cathode in step (1) is 0.05 to 3 kW, such as 0.05 kW, 0.1 kW, 0.5 kW, 1 kW, 1.5 kW, 2 kW, 2.5 kW or 3 kW, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0048] Preferably, the current of the magnetically adjustable multi-arc cathode in step (1) is 70 to 300A, such as 70A, 100A, 120A, 150A, 180A, 200A, 220A, 250A, 270A or 300A, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0049] Preferably, the power of the magnetically adjustable multi-arc cathode in step (1) is 0.5 to 20 kW, such as 0.5 kW, 1 kW, 3 kW, 5 kW, 8 kW, 10 kW, 12 kW, 15 kW, 18 kW or 20 kW, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0050] Preferably, the high content of sp in step (1) 3 The deposition time for the bonded carbon layer is 5 to 60 minutes, such as 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or 60 minutes, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0051] As a preferred technical solution of the present invention, the high content of sp in step (1) 3Before depositing the bonded carbon layer, an adhesive layer is first deposited on the surface of the cutting tool / drill bit.

[0052] Preferably, depending on the material of the adhesive layer, a magnetically adjustable multi-arc cathode is selected to control different atmosphere conditions and currents.

[0053] Preferably, when the adhesive layer is made of an elemental material, the pressure of the protective gas is controlled at 0.1–5 Pa, such as 0.1 Pa, 0.5 Pa, 1 Pa, 1.5 Pa, 2 Pa, 2.5 Pa, 3 Pa, 4 Pa, or 5 Pa, and the current of the magnetically adjustable multi-arc cathode is 20–300 A, such as 20 A, 50 A, 70 A, 100 A, 120 A, 150 A, 180 A, 200 A, 220 A, 250 A, 270 A, or 300 A, but is not limited to the listed values; other unlisted values ​​within their respective ranges are also applicable.

[0054] Preferably, when the adhesive layer is made of a nitride of the corresponding element, the pressure of the nitrogen gas is controlled at 0.5 to 5 Pa, such as 0.5 Pa, 1 Pa, 1.5 Pa, 2 Pa, 2.5 Pa, 3 Pa, 4 Pa, or 5 Pa, and the current of the magnetically adjustable multi-arc cathode is 20 to 300 A, such as 20 A, 50 A, 70 A, 100 A, 120 A, 150 A, 180 A, 200 A, 220 A, 250 A, 270 A, or 300 A, but it is not limited to the listed values. Other unlisted values ​​within their respective ranges are also applicable.

[0055] Preferably, when the adhesive layer is made of a carbide of the corresponding element, the pressure of the carbon-containing gas is controlled at 0.2 to 5 Pa, such as 0.2 Pa, 0.5 Pa, 1 Pa, 1.5 Pa, 2 Pa, 2.5 Pa, 3 Pa, 4 Pa, or 5 Pa, and the current of the magnetically adjustable multi-arc cathode is 20 to 300 A, such as 20 A, 50 A, 70 A, 100 A, 120 A, 150 A, 180 A, 200 A, 220 A, 250 A, 270 A, or 300 A, but it is not limited to the listed values. Other unlisted values ​​within their respective ranges are also applicable.

[0056] Preferably, when the adhesive layer is made of a carbonitride of the corresponding element, the pressure of the mixed gas containing carbon and nitrogen is controlled at 0.5 to 5 Pa, such as 0.5 Pa, 1 Pa, 1.5 Pa, 2 Pa, 2.5 Pa, 3 Pa, 4 Pa, or 5 Pa, and the current of the magnetically adjustable multi-arc cathode is 20 to 300 A, such as 20 A, 50 A, 70 A, 100 A, 120 A, 150 A, 180 A, 200 A, 220 A, 250 A, 270 A, or 300 A, but it is not limited to the listed values. Other unlisted values ​​within their respective ranges are also applicable.

[0057] Preferably, the carbon-containing gas includes acetylene and / or methane.

[0058] Preferably, when the adhesive layer comprises two or more layers, the above-mentioned single-layer deposition processes are combined and superimposed.

[0059] In this invention, depending on the type of adhesive layer, in addition to the target material corresponding to the element, nitrides, carbides or carbonitrides also require corresponding atmospheric conditions, such as nitrogen-containing gas or carbon-containing gas. For the former, nitrogen can be selected, and for the latter, simple organic gases such as methane, acetylene, etc. can be selected.

[0060] As a preferred technical solution of the present invention, the current of the magnetron sputtering cathode in step (2) is continuously increased from 0.1 to 2A, such as 0.1A, 0.3A, 0.5A, 0.8A, 1.0A, 1.2A, 1.5A, 1.8A or 2.0A, to 20 to 30A, such as 20A, 22A, 24A, 25A, 27A, 28A or 30A, but is not limited to the listed values. Other unlisted values ​​within their respective ranges are also applicable.

[0061] Preferably, the current of the magnetically regulated multi-arc cathode in step (2) is continuously reduced from 70 to 300A, such as 70A, 90A, 100A, 120A, 150A, 180A, 200A, 250A or 300A, to 20 to 80A, such as 20A, 30A, 40A, 50A, 60A, 70A, 80A, etc., but is not limited to the listed values. Other unlisted values ​​within their respective ranges are also applicable.

[0062] Preferably, the current of the magnetron sputtering cathode and the magnetically regulated multi-arc cathode in step (2) changes continuously or with a gradient.

[0063] Preferably, the deposition time of the gradient layer in step (2) is 2 to 120 min, such as 2 min, 5 min, 10 min, 20 min, 30 min, 45 min, 60 min, 80 min, 100 min or 120 min, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0064] In this invention, the deposition of the gradient layer, due to sp 3 Key and sp 2 Changes in bond content require corresponding real-time changes in cathode current, power, and other conditions; there is a corresponding relationship between the two, only based on sp... 3 Key and sp 2 The way the bond content changes determines whether the cathode current and power change continuously or in a gradient.

[0065] Preferably, the current of the magnetron sputtering cathode in step (3) is 20 to 30 A, such as 20 A, 22 A, 24 A, 25 A, 26 A, 28 A or 30 A, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0066] Preferably, the power of the magnetron sputtering cathode in step (3) is 10 to 30 kW, such as 10 kW, 12 kW, 15 kW, 18 kW, 20 kW, 22 kW, 25 kW, 27 kW or 30 kW, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0067] Preferably, the current of the magnetically adjustable multi-arc cathode in step (3) is 20 to 30A, such as 20A, 22A, 24A, 25A, 26A, 28A or 30A, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0068] Preferably, the power of the magnetically adjustable multi-arc cathode in step (3) is 0.05 to 1 kW, such as 0.05 kW, 0.1 kW, 0.2 kW, 0.3 kW, 0.4 kW, 0.5 kW, 0.6 kW, 0.8 kW or 1.0 kW, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0069] Preferably, the high content of sp in step (3) 2 The deposition time for the bonded carbon layer is 2 to 600 min, such as 2 min, 10 min, 30 min, 50 min, 75 min, 100 min, 150 min, 200 min, 300 min, 400 min, 500 min or 600 min, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0070] Thirdly, the present invention provides a cutting tool, the cutting tool including a drill bit and the aforementioned carbon-based coating, the drill bit including a spiral groove, a peripheral cutting edge and a drill tip, the spiral groove extending spirally from the drill tip to the end of the drill bit, and the carbon-based coating being divided into three cases: completely covering the drill bit area, partially covering the drill bit area, or partially covering the drill bit area and then adding an overall protective layer.

[0071] As a preferred technical solution of the present invention, the body diameter of the drill bit is 0.075 to 6 mm, for example, 0.075 mm, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm or 6 mm, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0072] Preferably, the axial length of the spiral groove accounts for more than 80% of the drill bit length, such as 80%, 85%, 90%, 95% or 100%, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0073] Preferably, the number of spiral grooves is at least one, such as one, two, or three.

[0074] Preferably, the depth of the spiral groove is 5% to 52% of the drill bit diameter, such as 5%, 10%, 15%, 20%, 25%, 30%, 40%, 50%, or 52%, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0075] As a preferred technical solution of the present invention, the carbon-based coating completely covers the drill bit area by covering the spiral groove, peripheral cutting edge and drill tip.

[0076] In this invention, this method requires full coverage of the drill bit area. When the tool size is small, the full coverage coating, especially when the coating thickness is large, has a significant impact on the drill bit diameter, which in turn greatly affects the chip removal capability and can easily lead to tool breakage. Therefore, this coating coverage method is mainly suitable for the processing of printed circuit boards with high wear resistance requirements and slightly lower chip removal requirements.

[0077] Preferably, the carbon-based coating partially covers the drill bit area by covering the peripheral cutting edge in the drill bit area.

[0078] Preferably, the length of the peripheral blade covered with the carbon-based coating accounts for 5% to 100% of the length of the spiral groove, such as 5%, 10%, 20%, 30%, 40%, 50%, 60%, 80%, or 100%, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0079] In this invention, the carbon-based coating only covers the peripheral cutting edge of the drill bit. The length of the coating on the peripheral cutting edge varies from the drill tip to the end of the spiral groove, depending on the processing material and the drill bit structure, and is limited to a certain length ratio. The spiral groove and the surface of the drill tip are not coated with carbon-based coating. This coating method is mainly for the processing of difficult-to-process printed circuit boards with large coating thickness and certain requirements for chip removal. While improving wear resistance, it does not affect the chip removal ability of the drill bit during deep hole processing.

[0080] Preferably, the partial coverage followed by an overall protective layer involves covering the peripheral cutting edge in the drill bit area and then depositing a low-friction coating layer on the whole.

[0081] Preferably, the thickness of the low-friction coating is 0.05 to 0.5 μm, such as 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm or 0.5 μm, and the coefficient of friction is less than 0.1, such as 0.1, 0.08, 0.06, 0.05, 0.04, 0.02 or 0.01, but is not limited to the listed values. Other unlisted values ​​within their respective ranges are also applicable.

[0082] In this invention, on the basis of the second coating, a carbon-based coating with an ultra-low coefficient of friction that is both wear-resistant and has a wear-resistant properties is deposited on the entire area of ​​the drill bit. Its coefficient of friction is much lower than that of conventional cemented carbide (0.6-0.8). This structural design is mainly for high-end, difficult-to-process printed circuit board applications where both the wear resistance and chip removal performance of the drill bit are extremely high. The low-friction coating is thin and has almost no effect on the core thickness, which can effectively improve the chip removal capability.

[0083] In this invention, the cutting tool is not limited to double-edged micro drills, but is also applicable to various standard and non-standard micro drills on the market. It can also be selected from end mills, reamers, broaches, molds, gears and other applications that require high wear resistance and lubrication.

[0084] Compared with the prior art, the present invention has the following beneficial effects:

[0085] (1) This invention is based on sp 3 Key and sp 2 Different bond contents are set to sp 3 Key and sp 2 The carbon layer is mainly composed of bonds; the former provides high hardness and wear resistance, while the latter has a low coefficient of friction and good lubricity.

[0086] (2) In this invention, sp 3 Key and sp 2 Gradient layers are set between carbon layers with bonds as the main components, so that the properties of the two layers can be gradually transitioned, avoiding poor bonding due to large differences in properties, improving the stability of carbon-based coatings, and reducing internal stress in the coating, avoiding the risk of easy breakage due to thickening of the coating, and achieving large thickness deposition.

[0087] (3) The carbon-based coating and tool structure described in this invention can effectively solve the processing problems of difficult-to-process high-frequency printed circuit boards, high-speed printed circuit boards and high-performance packaging substrates, which is conducive to the development of next-generation communication technology, chip industry and high-performance computing industry, and has a wide range of applications. Attached Figure Description

[0088] Figure 1 The gradient layer provided in this invention specification is a continuous gradient sp. 3Curve showing the variation of bond content along the thickness direction;

[0089] Figure 2 The gradient gradient of the gradient layer provided in this invention specification is sp 3 Curve showing the variation of bond content along the thickness direction;

[0090] Figure 3 This is a schematic diagram of the drill bit structure provided in Embodiment 1 of the present invention;

[0091] Figure 4 This is a partially enlarged view of the drill bit provided in Embodiment 1 of the present invention;

[0092] Figure 5 This is a schematic diagram of the drill tip structure in the drill bit provided in Embodiment 1 of the present invention;

[0093] Figure 6 This is a schematic diagram of the structure of the carbon-based coating provided in Embodiment 2 of the present invention;

[0094] Figure 7 This is a schematic diagram of the drill bit structure provided in Embodiment 2 of the present invention;

[0095] Figure 8 This is a partially enlarged view of the drill bit provided in Embodiment 2 of the present invention;

[0096] Figure 9 This is a schematic diagram of the drill tip structure in the drill bit provided in Embodiment 2 of the present invention;

[0097] Figure 10 This is a schematic diagram of the drill bit structure provided in Embodiment 3 of the present invention;

[0098] Figure 11 This is a partially enlarged view of the drill bit provided in Embodiment 3 of the present invention;

[0099] Figure 12 This is a schematic diagram of the drill tip structure in the drill bit provided in Embodiment 3 of the present invention;

[0100] Figure 13 The high content of sp in the carbon-based coating provided in Example 6 of this invention 3 XPS test results of the bonded carbon layer;

[0101] Figure 14 The high content of sp in the carbon-based coating provided in Example 6 of this invention 2 XPS test results of the bonded carbon layer;

[0102] Figure 15 This is a graph showing the breakage rate results when machining the E705G package substrate with different cutting tools, as provided in Embodiment 6 of the present invention.

[0103] Figure 16This is a diagram showing the wear results of E705G package substrates after being machined with different cutting tools, as provided in Embodiment 6 of the present invention.

[0104] Among them, 1-high content sp 3 2-Bound carbon layer, 3-Gradualized layer, 4-High sp content 2 4-Binding carbon layer, 5-Helical groove, 6-Circumferential cutting edge, 7-Drill tip. Detailed Implementation

[0105] To better illustrate the present invention and facilitate understanding of its technical solutions, the present invention is further described in detail below. However, the following embodiments are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.

[0106] The following are typical but non-limiting embodiments of the present invention:

[0107] Example 1:

[0108] This embodiment provides a carbon-based coating for a cutting tool surface and a cutting tool, wherein the carbon-based coating comprises, from the cutting tool surface outwards, a high content of SP... 3 Bonded carbon layer 1, graded layer 2, and high sp content 2 Bonded carbon layer 3, the high content of sp 3 sp in bonded carbon layer 1 3 The bond content is 52.9%, and the high content of sp... 2 sp in the bonded carbon layer 3 2 The bond content is 62.6%, and the sp from the inside to the outside of the gradient layer 2 is... 3 From high to low bond content, sp 2 The bond content increases from low to high.

[0109] The high content of sp 3 The thickness of the bonded carbon layer 1 is 0.15 μm, and the hardness is 52.1 GPa.

[0110] The high content of sp 2 The thickness of the bonded carbon layer 3 is 0.2 μm, and the hardness is 35.6 GPa.

[0111] The gradient layer 2 has a thickness of 0.2 μm, and the sp in the gradient layer 2 3 The bond content decreased linearly, uniformly, and gradually from 52.9% to 37.4%.

[0112] The cutting tool includes a drill bit and a carbon-based coating on the surface of the drill bit. A schematic diagram of the drill bit's structure is shown below. Figure 3 As shown, its enlarged partial view is as follows: Figure 4 As shown, it includes a spiral groove 5, a peripheral cutting edge 6, and a drill tip 7. The structural schematic diagram of the drill tip is shown below. Figure 5As shown, the spiral groove 5 extends spirally from the drill tip 7 to the end of the drill bit, and the carbon-based coating partially covers the drill bit area, that is, it covers the peripheral cutting edge 6 in the drill bit area.

[0113] The drill bit has a body diameter of 0.15 mm.

[0114] The axial length of the spiral groove 5 accounts for 100% of the drill bit length, and there are two spiral grooves 5. The depth of the spiral groove 5 accounts for 28% of the drill bit diameter.

[0115] The length of the peripheral blade 6 covered with a carbon-based coating is 50% of the length of the spiral groove 5.

[0116] Example 2:

[0117] This embodiment provides a carbon-based coating for a cutting tool surface and a cutting tool. A schematic diagram of the carbon-based coating is shown below. Figure 6 As shown, from the surface of the cutting tool outwards, it includes a high content of SP. 3 Bonded carbon layer 1, graded layer 2, and high sp content 2 Bonded carbon layer 3, the high content of sp 3 sp in bonded carbon layer 1 3 The bond content is 60.3%, and the high content of sp... 2 sp in the bonded carbon layer 3 2 The bond content is 75.4%, and the sp from the inside to the outside of the gradient layer 2 is... 3 From high to low bond content, sp 2 The bond content increases from low to high.

[0118] The high content of sp 3 The thickness of the bonded carbon layer 1 is 0.2 μm, and the hardness is 56.5 GPa.

[0119] The high content of sp 2 The thickness of the bonded carbon layer 3 is 0.3 μm, and the hardness is 22.5 GPa.

[0120] The gradient layer 2 has a thickness of 0.5 μm, and the sp in the gradient layer 2 3 The bond content decreased non-linearly and gradually from 60.3% to 24.6%.

[0121] The carbon-based coating also includes an adhesive layer 4, which is located between the carbon-based coating and the tool surface.

[0122] The adhesive layer 4 is made of chromium and has a thickness of 0.2 μm.

[0123] The cutting tool includes a drill bit and a carbon-based coating on the surface of the drill bit. A schematic diagram of the drill bit's structure is shown below. Figure 7 As shown, its enlarged partial view is as follows: Figure 8As shown, it includes a spiral groove 5, a peripheral cutting edge 6, and a drill tip 7. The structural schematic diagram of the drill tip is shown below. Figure 9 As shown, the spiral groove 5 extends spirally from the drill tip 7 to the end of the drill bit, and the carbon-based coating completely covers the drill bit area, that is, the spiral groove 5, the peripheral cutting edge 6 and the drill tip 7 are all covered.

[0124] The drill bit has a body diameter of 0.25 mm.

[0125] The axial length of the spiral groove 5 accounts for 95% of the drill bit length, and there are two spiral grooves 5. The depth of the spiral groove 5 accounts for 30% of the drill bit diameter.

[0126] Example 3:

[0127] This embodiment provides a carbon-based coating for a cutting tool surface and a cutting tool, wherein the carbon-based coating comprises, from the cutting tool surface outwards, a high content of SP... 3 Bonded carbon layer 1, graded layer 2, and high sp content 2 Bonded carbon layer 3, the high content of sp 3 sp in bonded carbon layer 1 3 The bond content is 71.7%, and the high content of sp... 2 sp in the bonded carbon layer 3 2 The bond content is 60.6%, and the gradient layer 2 has sp from the inside out. 3 From high to low bond content, sp 2 The bond content increases from low to high.

[0128] The high content of sp 3 The thickness of the bonded carbon layer 1 is 0.5 μm, and the hardness is 60.8 GPa.

[0129] The high content of sp 2 The thickness of the bonded carbon layer 3 is 1.5 μm, and the hardness is 33.9 GPa.

[0130] The gradient layer 2 has a thickness of 1.0 μm, and the sp in the gradient layer 2 3 The bond content decreased gradually from 71.7% to 30.4%.

[0131] The gradient layer 2 consists of two sp layers 3 It consists of gradient layers with different bond contents, and the thickness of a single gradient layer is 0.5 μm.

[0132] The cutting tool includes a drill bit and a carbon-based coating on the surface of the drill bit. A schematic diagram of the drill bit's structure is shown below. Figure 10 As shown, its enlarged partial view is as follows: Figure 11 As shown, it includes a spiral groove 5, a peripheral cutting edge 6, and a drill tip 7. The structural schematic diagram of the drill tip is shown below. Figure 12As shown, the spiral groove 5 extends spirally from the drill tip 7 to the end of the drill bit. The carbon-based coating partially covers the drill bit area and then an overall protective layer is added, that is, the peripheral cutting edge 6 in the drill bit area is covered and then a low-friction coating is deposited as a whole.

[0133] The drill bit has a body diameter of 0.9 mm.

[0134] The axial length of the spiral groove 5 accounts for 90% of the drill bit length, and there are two spiral grooves 5. The depth of the spiral groove 5 accounts for 25% of the drill bit diameter.

[0135] The length of the peripheral blade 6 covered with a carbon-based coating accounts for 80% of the length of the spiral groove 5.

[0136] The low-friction coating has a thickness of 0.1 μm, covers the entire surface of the drill bit area, and has a friction coefficient of 0.08.

[0137] Example 4:

[0138] This embodiment provides a carbon-based coating for a cutting tool surface and a cutting tool, wherein the carbon-based coating comprises, from the cutting tool surface outwards, a high content of SP... 3 Bonded carbon layer 1, graded layer 2, and high sp content 2 Bonded carbon layer 3, the high content of sp 3 sp in bonded carbon layer 1 3 The bond content is 76%, and the high content of sp 2 sp in the bonded carbon layer 3 2 The bond content is 77%, and the gradient layer 2 has sp from the inside to the outside. 3 From high to low bond content, sp 2 The bond content increases from low to high.

[0139] The high content of sp 3 The thickness of the bonded carbon layer 1 is 0.8 μm, and the hardness is 62.2 GPa.

[0140] The high content of sp 2 The thickness of the bonded carbon layer 3 is 0.9 μm, and the hardness is 20.6 GPa.

[0141] The gradient layer 2 has a thickness of 0.8 μm, and the sp in the gradient layer 2 3 The bond content changes non-linearly and gradually, decreasing from 76% to 23%.

[0142] The carbon-based coating also includes an adhesive layer 4, which is located between the carbon-based coating and the tool surface.

[0143] The adhesive layer 4 comprises a chromium adhesive layer and a chromium nitride adhesive layer in sequence. The thickness of the chromium adhesive layer is 0.2 μm, and the thickness of the chromium nitride adhesive layer is 0.3 μm.

[0144] The cutting tool includes a drill bit and a carbon-based coating on the surface of the drill bit. The drill bit includes a spiral groove 5, a peripheral cutting edge 6, and a drill tip 7. The spiral groove 5 extends spirally from the drill tip 7 to the end of the drill bit. The carbon-based coating completely covers the drill bit area, that is, it completely covers the spiral groove 5, the peripheral cutting edge 6, and the drill tip 7.

[0145] The drill bit has a body diameter of 2.0 mm.

[0146] The axial length of the spiral groove 5 accounts for 85% of the drill bit length, the number of spiral grooves 5 is one, and the depth of the spiral groove 5 accounts for 40% of the drill bit diameter.

[0147] Example 5:

[0148] This embodiment provides a carbon-based coating for a cutting tool surface and a cutting tool, wherein the carbon-based coating comprises, from the cutting tool surface outwards, a high content of SP... 3 Bonded carbon layer 1, graded layer 2, and high sp content 2 Bonded carbon layer 3, the high content of sp 3 sp in bonded carbon layer 1 3 The bond content is 65%, and the high content of sp 2 sp in the bonded carbon layer 3 2 The bond content is 55%, and the gradient layer 2 has sp from the inside to the outside. 3 From high to low bond content, sp 2 The bond content increases from low to high.

[0149] The high content of sp 3 The thickness of the bonded carbon layer 1 is 5 μm, and the hardness is 58.5 GPa.

[0150] The high content of sp 2 The thickness of the bonded carbon layer 3 is 4.5 μm, and the hardness is 40.5 GPa.

[0151] The high content of sp 2 The bonded carbon layer 3 is an element-doped carbon coating, with silicon as the dopant element.

[0152] The gradient layer 2 has a thickness of 2.5 μm, and the sp in the gradient layer 2 3 The bond content changes gradually, decreasing from 65% to 45%.

[0153] The gradient layer 2 consists of three sp layers 3 The layers are composed of gradient layers with different bond contents, namely 60%, 55% and 50%, with corresponding thicknesses of 0.8 μm, 0.9 μm and 0.8 μm, respectively.

[0154] The carbon-based coating also includes an adhesive layer 4, which is located between the carbon-based coating and the tool surface.

[0155] The adhesive layer 4 includes a silicon nitride adhesive layer, and the thickness of the adhesive layer 4 is 1 μm.

[0156] The cutting tool includes a drill bit and a carbon-based coating on the surface of the drill bit. The drill bit includes a spiral groove 5, a peripheral cutting edge 6, and a drill tip 7. The spiral groove 5 extends spirally from the drill tip 7 to the end of the drill bit. The carbon-based coating partially covers the drill bit area and then an overall protective layer is added, that is, the peripheral cutting edge 6 in the drill bit area is covered and then a low-friction coating is deposited on the whole.

[0157] The drill bit has a body diameter of 6 mm.

[0158] The axial length of the spiral groove 5 accounts for 80% of the drill bit length, and there are two spiral grooves 5. The depth of the spiral groove 5 accounts for 20% of the drill bit diameter.

[0159] The length of the peripheral blade 6 covered with a carbon-based coating is 100% of the length of the spiral groove 5.

[0160] The low-friction coating has a thickness of 0.5 μm, covers the entire surface of the drill bit area, and has a friction coefficient of 0.1.

[0161] Example 6:

[0162] This embodiment provides a method for preparing a carbon-based coating for a cutting tool surface, wherein the carbon-based coating is the carbon-based coating in Example 1, and the method includes the following steps:

[0163] (1) The drill bit is first ultrasonically cleaned using acetone, alcohol, and water as cleaning media, each used separately, for 20 minutes each. After cleaning, the drill bit is dried, then placed in a vacuum chamber, fixed on a fixture, and evacuated until the pressure drops to 1.0 × 10⁻⁶. -2 The pressure was controlled at 0.3 Pa by introducing argon gas. The magnetron sputtering cathode and the magnetically controlled multi-arc cathode were then activated. The current of the magnetron sputtering cathode was controlled at 0.4 A and the power at 0.2 kW, while the current of the magnetically controlled multi-arc cathode was controlled at 200 A and the power at 5 kW. Deposition was carried out on the surface of the tool drill bit for 20 minutes to obtain a high-content sp. 3 Bonded carbon layer;

[0164] (2) Based on step (1), the current of the magnetron sputtering cathode is continuously increased from 0.4A to 20A, and the current of the magnetically controlled multi-arc cathode is continuously decreased from 200A to 30A. After deposition for 20 minutes, a gradient layer is obtained.

[0165] (3) Based on step (2), argon gas is introduced to control the pressure to 0.85 Pa. The currents of the magnetron sputtering cathode and the magnetically controlled multi-arc cathode are then controlled. The current of the magnetron sputtering cathode is 20 A and the power is 12 kW. The current of the magnetically controlled multi-arc cathode is 30 A and the power is 0.8 kW. Deposition is carried out for 80 min to obtain a high content of sp. 2 A carbon layer is bonded to obtain a carbon-based coating, which covers the peripheral cutting edge position in the drill bit area.

[0166] The high content of sp in the carbon-based coating obtained in this embodiment 3 Bonded carbon layers and high sp content 2 XPS tests were performed on the bonded carbon layers, and the test results are as follows: Figure 13 and 14 As shown; a tool with a carbon-based coating was used to machine an E705G package substrate with 10,000 holes, and its performance was compared with that of a tool without a coating and a tool with a TiAlN coating. The tool breakage rate results are shown in the figure. Figure 15 As shown, the outer diameter of the tool changes after machining, and its wear is as follows. Figure 16 As shown.

[0167] In this embodiment, according to Figure 13 The curve in the figure shows that high content of sp can be calculated. 3 sp in the bonded carbon layer 3 The bond content is 52.9%, according to Figure 14 The curve in the figure shows that high content of sp can be calculated. 2 sp in the bonded carbon layer 2 The bond content is 62.6%; from Figure 15 It can be seen that the coated tool in this embodiment did not break after use, while the breakage rates of the uncoated tool and the tool coated with TiAlN were 3‰ and 2‰, respectively; Figure 16 It can be seen that after processing the 10,000-hole E705G package substrate, the outer diameter of the coated tool in this embodiment is reduced by only 2.1 μm, the outer diameter of the uncoated tool is reduced by 14.2 μm, and the outer diameter of the tool coated with TiAlN is reduced by 7.7 μm. It can be seen that the pure carbon coating in this embodiment has obvious wear resistance advantages.

[0168] In summary, the carbon-based coating reduces the tool breakage rate and improves tool wear resistance by increasing the lubricity and wear resistance of the tool surface, thus effectively extending the tool's service life.

[0169] Example 7:

[0170] This embodiment provides a method for preparing a carbon-based coating for a cutting tool surface, wherein the carbon-based coating is the carbon-based coating in Example 2, and the method includes the following steps:

[0171] (1) The drill bit was first ultrasonically cleaned using acetone, alcohol, and water as cleaning media, each used separately, for 30 minutes each. After cleaning, the drill bit was dried and then placed in a vacuum chamber, fixed on a fixture, and evacuated until the pressure dropped to 9.0 × 10⁻⁶. -3 Pa, and argon gas was introduced to control the pressure to 2.0 Pa. The magnetically adjustable multi-arc cathode was turned on, and the current of the magnetically adjustable multi-arc cathode was controlled to 60 A. The chromium bonding layer was deposited on the surface of the tool drill bit for 10 min.

[0172] The pressure was adjusted to 0.6 Pa, and the magnetron sputtering cathode and the magnetically regulated multi-arc cathode were simultaneously activated. The current of the magnetron sputtering cathode was controlled at 0.1 A and the power at 0.1 kW, while the current of the magnetically regulated multi-arc cathode was controlled at 150 A and the power at 10 kW. Deposition was carried out on the surface of the cutting tool for 30 minutes to obtain a high-content sp. 3 Bonded carbon layer;

[0173] (2) Based on step (1), the current of the magnetron sputtering cathode is continuously increased from 0.1A to 25A, and the current of the magnetically controlled multi-arc cathode is continuously decreased from 150A to 26A. After deposition for 50 minutes, a gradient layer is obtained.

[0174] (3) Based on step (2), argon gas was introduced to control the pressure to 1.5 Pa. The currents of the magnetron sputtering cathode and the magnetically controlled multi-arc cathode were further controlled. The current of the magnetron sputtering cathode was 30 A and the power was 28 kW. The current of the magnetically controlled multi-arc cathode was 20 A and the power was 0.2 kW. Deposition was carried out for 120 min to obtain a high content of sp. 2 A carbon layer is bonded to obtain a carbon-based coating that completely covers the drill bit area.

[0175] In this embodiment, the cutting tool covered with a carbon-based coating was used to process the difficult-to-machine EM390 printed circuit board, which can process 800 holes and the processing quality meets the requirements. Compared with the uncoated cutting tool, which can only process 200 holes, the processing life is increased to 4 times.

[0176] Example 8:

[0177] This embodiment provides a method for preparing a carbon-based coating for a cutting tool surface, wherein the carbon-based coating is the carbon-based coating in Example 3, and the method includes the following steps:

[0178] (1) The drill bit was first ultrasonically cleaned using acetone, alcohol, and water as cleaning media, each used separately, for 40 minutes each. After cleaning, the drill bit was dried and then placed in a vacuum chamber, fixed on a fixture, and evacuated until the pressure dropped to 1.0 × 10⁻⁶. -2The pressure was controlled to 0.1 Pa by introducing argon gas. The magnetron sputtering cathode and the magnetically regulated multi-arc cathode were then activated. The current of the magnetron sputtering cathode was controlled at 0.1 A and the power at 0.15 kW, while the current of the magnetically regulated multi-arc cathode was controlled at 300 A and the power at 18 kW. Deposition was carried out on the surface of the tool drill bit for 30 minutes to obtain a high-content sp. 3 Bonded carbon layer;

[0179] (2) Based on step (1), argon gas is introduced to control the pressure to 0.3 Pa. The current gradient of the magnetron sputtering cathode is increased directly from 0.4 A to 18 A. The current gradient of the magnetically controlled multi-arc cathode is decreased directly from 300 A to 70 A. After deposition for 4 min, the current of the magnetron sputtering cathode is increased directly from 18 A to 27 A. The current of the magnetically controlled multi-arc cathode is decreased directly from 70 A to 20 A. After deposition for 16 min, a gradient layer consisting of two gradient layers is obtained.

[0180] (3) Based on step (2), argon gas was introduced to control the pressure to 1.2 Pa. The currents of the magnetron sputtering cathode and the magnetically regulated multi-arc cathode were then controlled. The current of the magnetron sputtering cathode was 27 A and the power was 22 kW. The current of the magnetically regulated multi-arc cathode was 20 A and the power was 0.5 kW. Deposition was carried out for 60 min to obtain a high-content sp. 2 A carbon layer is bonded, thus obtaining a carbon-based coating.

[0181] The carbon-based coating covers the peripheral edge of the drill bit area, and then a low-friction coating is deposited to completely cover the drill bit area. Argon gas is introduced to control the pressure at 0.1 Pa, and the currents of the magnetron sputtering cathode and the magnetically regulated multi-arc cathode are controlled. The current of the magnetron sputtering cathode is 15 A and the power is 7.5 kW, and the current of the magnetically regulated multi-arc cathode is 100 A and the power is 2 kW. Deposition is carried out for 20 minutes to obtain the low-friction coating.

[0182] In this embodiment, the cutting tool covered with a carbon-based coating was used to process the difficult-to-machine EM526 printed circuit board, which can process 700 holes and the processing quality meets the requirements. Compared with the uncoated cutting tool, which can only process 150 holes, the processing life is increased to 4.67 times.

[0183] Example 9:

[0184] This embodiment provides a method for preparing a carbon-based coating for a cutting tool surface, wherein the carbon-based coating is the carbon-based coating in Example 4, and the method includes the following steps:

[0185] (1) The drill bit was first ultrasonically cleaned using acetone, alcohol, and water as cleaning media, each used separately, for 50 minutes each. After cleaning, the drill bit was dried, then placed in a vacuum chamber, fixed on a fixture, and evacuated until the pressure dropped to 5.0 × 10⁻⁶.-3 Pa, and neon gas was introduced to control the pressure to 3.0 Pa. The magnetically adjustable multi-arc cathode was turned on, and the current of the magnetically adjustable multi-arc cathode was controlled to 90 A. The chromium bonding layer was deposited on the surface of the tool drill bit for 20 min. The gas introduced was adjusted to nitrogen, the pressure was controlled to 3.5 Pa, the current of the magnetically adjustable multi-arc cathode was controlled to 90 A, and the deposition was carried out for 15 min to obtain the chromium nitride bonding layer.

[0186] The krypton gas pressure was adjusted to 0.3 Pa, and the magnetron sputtering cathode and the magnetically regulated multi-arc cathode were simultaneously activated. The current of the magnetron sputtering cathode was controlled at 0.2 A and the power at 0.05 kW, while the current of the magnetically regulated multi-arc cathode was controlled at 290 A and the power at 17 kW. Deposition continued for 30 min to obtain a high-content sp. 3 Bonded carbon layer;

[0187] (2) Based on step (1), the current of the magnetron sputtering cathode is continuously increased from 0.1A to 25A, and the current of the magnetically controlled multi-arc cathode is continuously decreased from 290A to 30A. After deposition for 50 minutes, a gradient layer is obtained.

[0188] (3) Based on step (2), krypton gas was introduced to control the pressure to 1.6 Pa. The currents of the magnetron sputtering cathode and the magnetically regulated multi-arc cathode were further controlled. The current of the magnetron sputtering cathode was 28.6 A and the power was 27.8 kW. The current of the magnetically regulated multi-arc cathode was 20 A and the power was 0.9 kW. Deposition was carried out for 350 min to obtain a high-content sp. 2 A carbon layer is bonded to obtain a carbon-based coating that completely covers the drill bit area.

[0189] In this embodiment, the cutting tool covered with a carbon-based coating is used to process aluminum-based printed circuit boards, which can process 15,000 holes and the processing quality meets the requirements. Compared with the cutting tool without a coating, which can only process 3,000 holes, the processing life is increased to 5 times.

[0190] As can be seen from the above embodiments, the present invention is based on sp 3 Key and sp 2 Different bond contents are set to sp 3 Key and sp 2 The carbon layer is mainly composed of bonds; the former provides high hardness and wear resistance, while the latter has a low coefficient of friction and good lubricity. This invention utilizes sp... 3 Key and sp 2A gradient layer is set between the carbon layers with bonds as the main components, so that the properties of the two layers gradually transition, avoiding poor bonding due to large differences in properties, improving the stability of the carbon-based coating, and reducing the internal stress in the coating. This avoids the risk of easy breakage due to thickening of the coating, and enables large-thickness deposition. The carbon-based coating and tool structure can effectively solve the processing problems of difficult-to-process high-frequency printed circuit boards, high-speed printed circuit boards, and high-performance packaging substrates, and has a wide range of applications.

[0191] The applicant declares that the present invention is illustrated through the above embodiments to describe the detailed products and methods of the present invention, but the present invention is not limited to the detailed products and methods described above, that is, it does not mean that the present invention must rely on the detailed products and methods described above to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions for the products of the present invention, additions to auxiliary structures, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a carbon-based coating for a cutting tool surface, characterized in that, The method for preparing the carbon-based coating includes the following steps: (1) After fixing the tool drill bit, a vacuum is drawn and a protective gas is introduced to control the pressure. The magnetron sputtering cathode and the magnetically modulated multi-arc cathode are turned on to control the cathode current and deposit a high content of sp on the surface of the tool drill bit. 3 Bonded carbon layer; (2) Based on step (1), the current of the magnetron sputtering cathode is continuously increased and the current of the magnetically controlled multi-arc cathode is continuously decreased to deposit a gradient layer; (3) Based on step (2), continue to control the current of the magnetron sputtering cathode and the magnetically controlled multi-arc cathode to deposit a high content of sp. 2 A carbon layer is bonded to obtain a carbon-based coating. In this process, an angle is formed between the magnetron sputtering cathode and the magnetically adjustable multi-arc cathode, the angle of which is 20~180°, and the angle between the central axes of the magnetron sputtering cathode and the magnetically adjustable multi-arc cathode intersects at the surface of the cutting tool. In step (1), the current of the magnetron sputtering cathode is 0.1~2A, and in step (2), the current of the magnetron sputtering cathode is continuously increased from 0.1~2A to 20~30A. In step (1), the current of the magnetically regulated multi-arc cathode is 70~300A. In step (2), the current of the magnetically regulated multi-arc cathode is continuously reduced from 70~300A to 20~60A. The carbon-based coating comprises, from the surface of the cutting tool outwards, a high content of SP. 3 Bonded carbon layer, gradient layer and high sp content 2 Bonded carbon layer, the high content of sp 3 sp 3 The bond content is 50-80%, and the high content of sp 2 sp 2 The bond content is 50-80%, and the sp from the inside to the outside of the gradient layer is... 3 From high to low bond content, sp 2 The bond content increases from low to high.

2. The preparation method according to claim 1, characterized in that, The high content of sp 3 The thickness of the bonded carbon layer is 0.1~5μm.

3. The preparation method according to claim 1, characterized in that, The high content of sp 3 The hardness of the bonded carbon layer is 45~65 GPa.

4. The preparation method according to claim 1, characterized in that, The high content of sp 2 The thickness of the bonded carbon layer is 0.1~5μm.

5. The preparation method according to claim 1, characterized in that, The high content of sp 2 The hardness of the bonded carbon layer is 20~45 GPa.

6. The preparation method according to claim 1, characterized in that, The thickness of the gradient layer is 0.1~3μm.

7. The preparation method according to claim 1, characterized in that, sp in the gradient layer 3 Bond content increased from high sp content 3 sp 3 The content of the bond decreased to a high content of sp 2 sp 3 Bond content.

8. The preparation method according to claim 1, characterized in that, sp in the gradient layer 3 Bond content or sp 2 The bond content changes continuously or gradually.

9. The preparation method according to claim 8, characterized in that, During the continuous gradual change, sp 3 Bond content or sp 2 The bond content changes linearly or nonlinearly.

10. The preparation method according to claim 8, characterized in that, During the gradient transition, the gradient layer consists of at least two sp layers. 3 It consists of gradient layers with different bond contents.

11. The preparation method according to claim 10, characterized in that, The thickness of a single gradient layer is 0.02~1μm.

12. The preparation method according to claim 1, characterized in that, The high content of sp 2 The bonded carbon layer includes a pure carbon coating or an element-doped carbon coating.

13. The preparation method according to claim 12, characterized in that, The doped elements include any one or a combination of at least two of silicon, nitrogen, hydrogen, chromium, titanium, tantalum, molybdenum, niobium, or aluminum.

14. The preparation method according to claim 1, characterized in that, The carbon-based coating also includes an adhesive layer located between the carbon-based coating and the tool surface.

15. The preparation method according to claim 14, characterized in that, The adhesive layer is made of any one or a combination of at least two of the following: an element, a nitride of the corresponding element, a carbide of the corresponding element, or a carbonitride of the corresponding element.

16. The preparation method according to claim 15, characterized in that, The elemental substance includes any one or a combination of at least two of chromium, titanium, molybdenum, tungsten, tantalum, vanadium, or silicon.

17. The preparation method according to claim 14, characterized in that, The adhesive layer has at least one layer, and the thickness of each adhesive layer is 0.1~1μm.

18. The preparation method according to claim 1, characterized in that, Before fixing the cutting tool in step (1), it must be cleaned, including ultrasonic cleaning.

19. The preparation method according to claim 18, characterized in that, The cleaning medium includes any one or a combination of at least two of acetone, alcohol, or water, and the medium may be used alone.

20. The preparation method according to claim 18, characterized in that, The cleaning time is independently 10~60 minutes.

21. The preparation method according to claim 20, characterized in that, The cutting tools and drill bits are dried after cleaning.

22. The preparation method according to claim 1, characterized in that, In step (1), the cutting tool is placed in a vacuum chamber and fixed on a fixture.

23. The preparation method according to claim 1, characterized in that, After vacuuming in step (1), the pressure drops to 1.0 × 10⁻⁶. -2 Below Pa.

24. The preparation method according to claim 1, characterized in that, The protective gas in step (1) includes an inert gas.

25. The preparation method according to claim 1, characterized in that, The pressure after introducing the protective gas in step (1) is 0.1~5 Pa.

26. The preparation method according to claim 1, characterized in that, The power of the magnetron sputtering cathode in step (1) is 0.05~3kW.

27. The preparation method according to claim 1, characterized in that, The power of the magnetically regulated multi-arc cathode in step (1) is 0.5~20kW.

28. The preparation method according to claim 1, characterized in that, The high content of sp mentioned in step (1) 3 The deposition time for the bonded carbon layer is 5 to 60 minutes.

29. The preparation method according to claim 1, characterized in that, The high content of sp mentioned in step (1) 3 Before depositing the bonded carbon layer, an adhesive layer is first deposited on the surface of the cutting tool / drill bit.

30. The preparation method according to claim 29, characterized in that, Depending on the material of the adhesive layer, a magnetically adjustable multi-arc cathode is selected to control different atmosphere conditions and currents.

31. The preparation method according to claim 30, characterized in that, When the adhesive layer is made of an element, the pressure of the protective gas is controlled at 0.1~5Pa, and the current of the magnetically regulated multi-arc cathode is 20~300A.

32. The preparation method according to claim 31, characterized in that, When the adhesive layer is made of a nitride of a corresponding element, the pressure of nitrogen gas is controlled at 0.5~5Pa, and the current of the magnetically adjusted multi-arc cathode is 20~300A.

33. The preparation method according to claim 32, characterized in that, When the adhesive layer is made of a carbide of the corresponding element, the pressure of the carbon-containing gas is controlled at 0.2~5Pa, and the current of the magnetically adjusted multi-arc cathode is 20~300A.

34. The preparation method according to claim 33, characterized in that, When the adhesive layer is made of carbonitride of the corresponding element, the pressure of the mixed gas containing carbon and nitrogen is controlled at 0.5~5Pa, and the current of the magnetically regulated multi-arc cathode is 20~300A.

35. The preparation method according to claim 34, characterized in that, The carbon-containing gas includes acetylene and / or methane.

36. The preparation method according to claim 35, characterized in that, When the adhesive layer comprises two or more layers, the single-layer deposition process is combined and stacked.

37. The preparation method according to claim 1, characterized in that, In step (2), the current of the magnetron sputtering cathode and the magnetically regulated multi-arc cathode changes continuously or in a gradient.

38. The preparation method according to claim 1, characterized in that, The deposition time of the gradient layer in step (2) is 2~120 min.

39. The preparation method according to claim 1, characterized in that, The current of the magnetron sputtering cathode in step (3) is 20~30A.

40. The preparation method according to claim 1, characterized in that, The power of the magnetron sputtering cathode in step (3) is 10~30kW.

41. The preparation method according to claim 1, characterized in that, The current of the magnetically regulated multi-arc cathode in step (3) is 20~30A.

42. The preparation method according to claim 1, characterized in that, The power of the magnetically regulated multi-arc cathode in step (3) is 0.05~1kW.

43. The preparation method according to claim 1, characterized in that, The high content of sp in step (3) 2 The deposition time for the bonded carbon layer is 2 to 600 minutes.

44. A cutting tool, characterized in that, The cutting tool includes a drill bit and a carbon-based coating prepared according to any one of claims 1-43. The drill bit includes a spiral groove, a peripheral cutting edge, and a drill tip. The spiral groove extends spirally from the drill tip to the end of the drill bit. The carbon-based coating is divided into three types: completely covering the drill bit area, partially covering the drill bit area, or partially covering the drill bit area and then adding an overall protective layer.

45. The cutting tool according to claim 44, characterized in that, The body diameter of the drill bit is 0.075~6mm.

46. ​​The cutting tool according to claim 44, characterized in that, The axial length of the spiral groove accounts for more than 80% of the drill bit length.

47. The cutting tool according to claim 44, characterized in that, The number of spiral grooves is at least one.

48. The cutting tool according to claim 44, characterized in that, The depth of the spiral groove is 5-52% of the drill bit diameter.

49. The cutting tool according to claim 44, characterized in that, The carbon-based coating completely covers the drill bit area, including the spiral grooves, peripheral cutting edges, and drill tip.

50. The cutting tool according to claim 44, characterized in that, The carbon-based coating partially covers the drill bit area by covering the peripheral cutting edge within the drill bit area.

51. The cutting tool according to claim 50, characterized in that, The length of the peripheral blade covered with a carbon-based coating accounts for 5 to 100% of the length of the spiral groove.

52. The cutting tool according to claim 44, characterized in that, The partial coverage followed by an overall protective layer involves covering the peripheral cutting edge in the drill bit area and then depositing a low-friction coating layer over the entire surface.

53. The cutting tool according to claim 52, characterized in that, The thickness of the low-friction coating is 0.05~0.5μm, and the coefficient of friction is less than 0.1.

Citation Information

Patent Citations

  • Substrate coated with a layered structure comprising a tetrahedral carbon layer and a softer outer layer

    CN101432462A

  • Diamond-like based nano-composite coated cutting tool and preparation method thereof

    CN103317793A

  • Preparation method of nano composite GNCD-cBN multilayer coated cutter having toughening mechanism

    CN108220916A

  • Multi-layer composite carbon coating as well as preparation method and application thereof

    CN114665114A

  • High-performance drill bit

    CN201770765U